2021
DOI: 10.1021/acs.inorgchem.1c02122
|View full text |Cite
|
Sign up to set email alerts
|

Aluminosilicate Nanosponges: Synthesis, Properties, and Application Prospects

Abstract: A simple one-step method is presented for fabricating inorganic nanosponges with a kaolinite [Al2Si2O5(OH)4] structure. The nanosponges were synthesized by the hydrothermal treatment of aluminosilicate gels in an acidic medium (pH = 2.6) at 220 °C without using organic cross-linking agents, such as cyclodextrin or polymers. The formation of the nanosponge morphology was confirmed by scanning electron microscopy, and the assignment of the synthesized aluminosilicates to the kaolinite group was confirmed by X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 60 publications
0
9
0
2
Order By: Relevance
“…Previous studies of the influence of synthesis conditions on the crystallization of aluminosilicates of the kaolinite subgroup with a given morphology [ 23 , 24 ] made it possible to determine the optimal conditions for obtaining samples with one predominant morphology. Thus, it was found that an alkaline environment (pH 12) favors the formation of particles with a predominantly spherical morphology, an acidic environment and a synthesis duration of 1 to 3 days (pH 2.6) favors the crystallization of particles with a nanosponge morphology.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies of the influence of synthesis conditions on the crystallization of aluminosilicates of the kaolinite subgroup with a given morphology [ 23 , 24 ] made it possible to determine the optimal conditions for obtaining samples with one predominant morphology. Thus, it was found that an alkaline environment (pH 12) favors the formation of particles with a predominantly spherical morphology, an acidic environment and a synthesis duration of 1 to 3 days (pH 2.6) favors the crystallization of particles with a nanosponge morphology.…”
Section: Resultsmentioning
confidence: 99%
“…The presence or absence of toxicity in inorganic compounds may be due to various factors [ 23 ]. Thus, it was shown in [ 62 ] that mesoporous silica nanoparticles show lower hemolytic activity than their nonporous counterparts of similar size.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Направленный гидротермальный синтез можно рассматривать как пример природоподобных технологий, позволяющий получать материалы, обладающие всеми достоинствами природных глинистых материалов, таких как высокая сорбционная ёмкость и способность к ионному обмену, и не обладающие их недостатками, к которым можно отнести непостоянство фазового и химического состава и, как следствие, наличие токсичности. В лаборатории химии силикатных сорбентов ИХС РАН в результате многолетних исследований механизмов кристаллизации слоистых силикатов в гидротермальных условиях, изучения их взаимной трансформации и самоорганизации определены условия получения целой линейки алюмосиликатов -аналогов природных минералов, качественно отличающихся от них набором определенных заданных характеристик, контроль над которыми может быть осуществлен правильным подбором соответствующих условий синтеза [1][2][3][4][5][6]. В качестве основных объектов исследований были выбраны слоистые силикаты со структурой монтмориллонита Na2x(Al2(1-x), Mg2x)Si4O10(OH)2 .…”
Section: результатыunclassified